The Development of Scout Activities Management with Participation for School in Tha Chang Network Under the Surat Thani Primary Educational Service Area Office 2 - Chaikaew, Wisanu (Rajapark Journal, 2025)
The objectives of this study were: 1) to study the operational conditions of the Boy Scout Administration, 2) to develop the Boy Scout management processes, and 3) to evaluate the results of the development of the Scout activities management with participation for schools in Tha Chang Network under the Surat Thani Primary Educational Service Area Office 2. The research process consists of 1) studying the operational conditions of the Boy Scout administration. The population includes educational institution administrators and responsible scouting teachers, totaling 158 people. The tool used for data collection is a questionnaire. 2) The development of scout management processes using action research consists of three steps: Plan, Act, Observe, and Reflect. Target groups include educational institution administrators and responsible teachers, specifically scouting teachers, totaling 34 individuals. A knowledge test will be administered, and the t-test will be used as the statistical method. The tools used are skills assessment and satisfaction assessment form. Data were analyzed using basic statistics, including mean and standard deviation. The research results found that 1) The condition of scouting administration was at a moderate level overall and in each aspect. 2) Results of the development of the scouting administration process found that the average value after development was higher than before development. Statistically significant at the .01 level, and 3) the development evaluation results and satisfaction were at the highest level with an average of 4.82